2021
DOI: 10.1136/oemed-2021-107667
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among UK university staff and postgraduate students in the early stages of the COVID-19 pandemic

Abstract: ObjectivesTo characterise the baseline King’s College London Coronavirus Health and Experiences of Colleagues at King’s cohort and describe patterns of probable depression and anxiety among staff and postgraduate research students at a large UK university in April/May 2020.MethodsAn online survey was sent to current staff and postgraduate research students via email in April 2020 (n=2590). Primary outcomes were probable depression and anxiety, measured with the Patient Health Questionnaire-9 and Generalised An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 40 publications
5
31
3
Order By: Relevance
“…Literature also reported evidence of the negative effects of teleworking on family routines during the pandemic, such as the perception of a loss of boundaries between private and professional life and greater work-family conflict [5,49,52,53]. Several studies also showed an association between having young children and psychological distress [9,54], which seems stronger among females [31]. Teleworkers were more likely to report distress resulting from work-family conflict and being in confined spaces at home [45].…”
Section: Academic Staff Well-being During the Pandemicmentioning
confidence: 99%
“…Literature also reported evidence of the negative effects of teleworking on family routines during the pandemic, such as the perception of a loss of boundaries between private and professional life and greater work-family conflict [5,49,52,53]. Several studies also showed an association between having young children and psychological distress [9,54], which seems stronger among females [31]. Teleworkers were more likely to report distress resulting from work-family conflict and being in confined spaces at home [45].…”
Section: Academic Staff Well-being During the Pandemicmentioning
confidence: 99%
“…Since the beginning of the COVID-19 pandemic in the spring 2020, an abundance of online surveys has been conducted examining people’s stress and anxiety levels, vaccination willingness, attitudes towards the national pandemic management and social behavior, among others [13] , [14] , [15] , [16] . Surprisingly, many survey reports did not provide survey response rates, yet those that did, reported survey response rates ranging from 8 to 50% [7] , [13] .…”
Section: Discussionmentioning
confidence: 99%
“…The target population was all staff and PGR students at KCL. Described in detail elsewhere, 15 survey respondents represented the population in terms of age, but female gender and White ethnicity were over-represented. We used administrative information for staff and PGR student populations to construct a ‘baseline weight’ accounting for differences in age, gender and ethnicity between the baseline cohort and the target population.…”
Section: Methodsmentioning
confidence: 99%
“… 14 We have previously reported on symptoms of depression and anxiety collected at the baseline questionnaire in April 2020. 15 …”
Section: Introductionmentioning
confidence: 99%